CODE-SWITCHING IN YOUTH SOCIAL MEDIA DISCOURSE AND ITS PEDAGOGICAL IMPLICATIONS (SCIENCE TIME JOURNAL, 2026)
This article provides a comprehensive analysis of code-switching in youth social media discourse and examines its pedagogical implications in language teaching. With the rapid development of globalization and digital communication technologies, social media platforms such as Telegram, Instagram, and TikTok have become dominant spaces where young people actively engage in multilingual communication. As a result, the frequent alternation between languages—particularly Uzbek, Russian, and English—has become a defining feature of youth discourse, influencing their linguistic behavior and communicative competence. The study identifies major types of code-switching, including intra-sentential, inter-sentential, and tag-switching, and analyzes their semantic and pragmatic functions in online interactions. Special attention is given to the impact of code-switching on students’ language proficiency, academic discourse, and linguistic awareness. The findings suggest that code-switching should not be viewed solely as a linguistic deficiency; instead, when applied strategically, it can serve as a valuable pedagogical resource in multilingual classrooms. The article also proposes practical teaching strategies for educators to manage and integrate code-switching effectively into the learning process. These strategies aim to enhance students’ communicative competence while maintaining standard language norms. The research contributes to the field of sociolinguistics and language pedagogy by offering insights into youth language practices and their relevance to modern educational contexts.